International Jazz Day 2015.
Edna Manley College of the Visual and Performing Arts celebrates International Jazz Day 2015, Jazz concert on the East Lawns of Devon House on Wednesday April 30, 2015 at 7:00 p.m.
Posters are located in drawer #1.
Keywords: Arts -- Music -- Jamaica; Posters -- Jamaica